Bermain origami untuk melatih keterampilan motorik halus anak usia dini - Sandra Adetya; Fathana Gina (University of Muhammadiyah Malang, 2022)
The development of fine motor skills in children age 2-12 years old is important because it is related to other developmental tasks, such as independence, cognitive abilities, etc. In fact, not many parents have sufficient knowledge of aspects of child development and how to develop it. The program that will be carried out in community service is playing origami to practice fine motor skills. The community service partner is Sekolah Rakyat Bekasi, a community formed by student volunteers who care about the development and education of underprivileged children living on the river banks in the Teluk Buyung area, Bekasi Utara. The purpose of playing origami in particular is to provide the experience of playing origami and provide the experience of playing origami and provide stimulation to enhance fine motor skills in children at Sekolah Rakyat Bekasi. There are 30 children who joined the program. The results of the service activity showed that the children succeeded in folding origami according to the instructions given, and participants benefited from playing with origami, including practicing fine motor skills and concentration.